Characterization of Thielaviopsis paradoxa isolates from oil palm in Colombia, Ecuador and Brazil - Álvarez, Elizabeth; Llano Rodríguez, Germán Alberto; Loke, John Bernard; Chacón Sánchez, María I. (Wiley, 2012)
Ceratocystis paradoxa (Anamorph: Thielaviopsis paradoxa) is parasitic on a range of economic and food crops and is the cause of dry basal rot, a limiting disease in oil palm. The objective of this study was to determinate the pathogenic and genetic diversity of Thielaviopsis isolates from oil palms in Colombia, Ecuador and Brazil. A total of 164 strains of Thielaviopsis paradoxa were characterized using pathogenicity tests, random amplified polymorphic DNA (RAPD) markers and PCR sequencing of the internal transcribed spacer (ITS) region of 5.8 S ribosomal DNA. Oil palm seedlings were inoculated by injecting the base of stems in the seedling stage with a fungal suspension and severity scores of disease reactions were evaluated. PCR amplification of the ITS region resulted in a 590 base pair (bp) product. Digestion of the PCR product with two restriction enzymes produced three restriction patterns, which according to ITS sequences could be classified as T. paradoxa. Six RAPD primers gave polymorphic bands in T. paradoxa. Population structure analyses of the RAPD data suggested that most of the isolates obtained in this study belonged to a single population. The genetic diversity of the isolates from South America was intermediate, and therefore, T. paradoxa is likely to be predominantly clonal compared with Ceratocystis species. Sporadic sexual reproduction may occur for T. paradoxa but is secondary to clonal reproduction. Data on pathogen diversity will provide information on breeding strategies and population structures.